RANCANG BANGUN INFRA RED BERBASIS ARDUINO UNO DENGAN SENSOR JARAK - Christian Immanuel Gultom; Harold Situmorang (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2019)
The exiting infrared therapy equipment is still operated manually and there is no long data and distance to use infrared lights(the Philips brand infrared manual type R925 UNP 20002). This raises the risk of negligence in monitoring the length of the therapy and recording the usee of lights which in turn can endanger patients and effect of therapy received . To overcome this problem, an infrared light therapy device based on Arduino Mega microcontroller is desaiengd which is equipped with setting the irradiation time and the illumination distance to be able to help physiotherapy operators, especially patiens who need infrared devices without the fear of side effects due neglect of the physiotherapy operator. The effect of the proximity sensor on the patient is that the farther the object or patient is from the patient, the temperature will decrase and vice versa, the closer the distance to the object, the hotter the temperature.